The role of mass media in the process of settlement of social problem of people with disabilities in modern Ukrainian society - Husakova, Kateryna (Видавництво Львівської політехніки, 2017)
This article contains the results of research on the role of the media in the process of settlement of social problems of people with disabilities, the results of content analysis of periodicals on this issue, and the importance of social advertising (PSA) in this process
Keywords: mass media; social problem; people with disabilities; social aspect